2007
DOI: 10.1038/ncb1619
|View full text |Cite
|
Sign up to set email alerts
|

The Smc5–Smc6 complex and SUMO modification of Rad52 regulates recombinational repair at the ribosomal gene locus

Abstract: Homologous recombination (HR) is crucial for maintaining genome integrity by repairing DNA double-strand breaks (DSBs) and rescuing collapsed replication forks. In contrast, uncontrolled HR can lead to chromosome translocations, loss of heterozygosity, and deletion of repetitive sequences. Controlled HR is particularly important for the preservation of repetitive sequences of the ribosomal gene (rDNA) cluster. Here we show that recombinational repair of a DSB in rDNA in Saccharomyces cerevisiae involves the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
404
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 359 publications
(426 citation statements)
references
References 39 publications
22
404
0
Order By: Relevance
“…However, we may have uncovered a more general role of heavy sumoylation in nucleolar maintenance, by showing that the bulk of SUMO is concentrated in the nucleolus in the smt4Δ mutant. While some reports showed that increase in sumoylation correlates with proteins leaving the nucleolus (Mo et al 2002;D'Amours et al 2004;Torres-Rosell et al 2007), in neither case, the localization of the sumoylated pool was tracked.…”
Section: Discussionmentioning
confidence: 98%
“…However, we may have uncovered a more general role of heavy sumoylation in nucleolar maintenance, by showing that the bulk of SUMO is concentrated in the nucleolus in the smt4Δ mutant. While some reports showed that increase in sumoylation correlates with proteins leaving the nucleolus (Mo et al 2002;D'Amours et al 2004;Torres-Rosell et al 2007), in neither case, the localization of the sumoylated pool was tracked.…”
Section: Discussionmentioning
confidence: 98%
“…Temperature-sensitive mutants of Smc6 have been shown to affect the stability of repetitive sequences in budding yeast by influencing their repair [35,36]. These observations have been recently extended to human cells, where the Smc5-Smc6 complex has been shown to play a role in alternative lengthening of telomeres ALT pathways, which are mediated by homologous recombination events [37].…”
Section: Introductionmentioning
confidence: 87%
“…For example, the cohesion defect impairs sister chromatid recombination [31,66], increasing intra-chromatid recombination in the tandem array of ribosomal repeats [36]. Recent work even suggested that Smc5-Smc6 would be required for the efficient loading of cohesin to DSB sites [67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, DSBs within the highly repetitive ribosomal RNA genes (rDNA) can lead to unequal sister chromatid exchange events, compromise chromosome stability and shorten cellular lifespan [4][5][6][7] . DSBs within rDNA repeats were found to transiently exit the Rad52/recombination-repressive environment of the nucleolus in which they typically reside to undergo repair without compromising genome integrity 8,9 . In flies, heterochromatic DSBs exit their Rad51/recombinationrepressive subnuclear domain to undergo repair 10 .…”
mentioning
confidence: 99%